PERLAWANAN ETNIS MUSLIM ROHINGYA TERHADAP KEBIJAKAN DISKRIMINATIF PEMERINTAH BURMA-MYANMAR - , GULIA ICHIKAYA MITZY; , Rochdi Mohan Nazala, MSA, M.Litt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to give an explanation that there are resistances by Muslim Rohingya in facing of discriminatory treatment or policies in Burma- Myanmar. Where there are differences in the pattern of resistance that was conducted over the span of 60 years or two periods of Government, namely the Military Junta and the Transition to Democracy. This research was based on cases which concerning discrimination against Muslim Rohingya in Burma-Myanmar. In addition, the writing or preaching majority so far shows about the suffering they have experienced, not what they have done in response to the policy or discriminatory treatment in Burma- Myanmar. In this research, author used qualitative methods with literature study to collect data and also inductive as an analysis technique. Several theories were used to analyse this research, such as ethnic minorities, social movement theory, social identity and discrimination to guide and strengthen the main argument of this research. As a result, it is known that there are differences in pattern of resistances conducted during two periods of Government. Patterns which conducted during the first period or in Military Junta era over the opposition to the Government directly, such as revolts or to migrate due to the policies of the Burmese Citizenship Law in 1982. Whereas, in the second period of transition to democracy, the resistance patterns do tend to be due to the prolonged ethnic conflicts which eventually led to resistance patterns of migration and rejection of the use of the Bengali identity in order to gain citizenship rights offered the Government of Burma-Myanmar.